Effect Of Annealing On Microstructure And Mechanical Properties Of 0.06% Carbon Steel - Phoumiphon, Nordala (2017)
The present study is aimed to examine the microstructure and mechanical properties of low-carbon (0.06% C) steel against several heat treatment and cold worked processes. The process was started with three different heat treatments; Air Cooling (AC), Ice-Water Quenching (IWQ), and Step Quenching (SQ) prior 75% cold rolling. All cold-rolled specimens were subcritical and intercritical annealing. The results show that the IWQ is the best method to start initial microstructure compared to AC and SQ method. The optimum of subcritical annealing temperature is at 525ºC. At this temperature (525ºC), ultrafine ferrite grains are obtained ( 500 nm). Tensile strength and microhardness are higher than as-received condition about 89% and 79%, respectively. Furthermore, it was found that the optimum intercritical annealing temperature is at 800ºC. At this temperature (800ºC), a good combination of ferrite and martensite are formed. The tensile strength and microhardness are higher than the as-received specimen about 81% and 104%, respectively.